The incidence of failed back surgery syndrome varies between clinical setting and procedure type. (September 2022) - Stanton, Eloise W.; Chang, Ki-Eun; Formanek, Blake; Buser, Zorica; Wang, Jeffrey
Highlights: Failed back surgery syndrome (FBSS) is a significant of patient morbidity. There is a lack of consensus regarding the diagnosis of FBSS. FBSS is more common in the inpatient vs. outpatient setting. FBSS is more common after multi-level procedures than single-level procedures. FBSS is common in decompression procedures. Abstract: Background: Failed back surgery syndrome (FBSS) is a significant cause of lumbar disability and is associated with severe patient morbidity. As the etiology of FBSS is not completely elucidated, the risk factors and evaluation of patients with FBSS remains challenging. Our analysis of a wide variety of operation types, clinical setting, and their correlation to FBSS seeks to allow fellow clinicians to be aware of the potential risk factors that leads to this devastating diagnosis. Methods: Data were obtained for patients undergoing anterior lumbar fusion, posterior lumbar fusion, or decompression procedures from January 2010 to December 2017 from the Mariner insurance database. Rates of FBSS at six- and twelve-months post-surgery were determined for patients undergoing single/multilevel procedures according to place of service, and approach/procedure type. Results: From 2010 to 2017, 102, 047 patients underwent lumbar fusion or decompression surgery (54% decompression procedures, 36% posterior fusions, and 8.9% anterior fusions). 5.4% of patients were diagnosed with FBSS within six months of the index procedure, and 8.4% were diagnosed with FBSS within twelve months. FBSS was higher in the inpatient (6.0%) vs. outpatient (4.3%) cohort. Among the surgical techniques, multi-level procedures had significantly higher rates of FBSS than single-level procedures, the highest being 10% in multi-level inpatient decompression procedures (p < 0.05). Conclusion: The highest rates of FBSS occurred in in the elderly (age group 70–74), for those patients whose index procedure was received in an inpatient setting, as well as for those receiving a multi-level surgery.